Let the Customers Speak Their Hearts Out: The Role of Verbosity and Emotions in Online Viewer-to-Viewer Engagement - Fahad Mansoor Pasha; Fatima Habib; Komal Kamran; Akbar Azam; Zeeshan Ali; Dildar Hussain (Human Behavior and Emerging Technologies)
This study examines the combined impact of emotions, emojis, and verbosity on online viewer-to-viewer engagement, focusing on their interaction in shaping engagement behaviors. Using sentiment analysis with the Syuzhet package in R Studio and logistic regression on over 15,000 YouTube comments from the “YouTube Ads Leaderboard: 2021 Cannes Edition,” this research identifies key drivers of replies to initial comments. Results reveal that verbosity significantly enhances engagement, while emojis generally diminish it. Arousal-inducing emotions, such as anticipation and anger, positively influence engagement but are moderated by comment length. These findings extend the understanding of digital engagement by integrating textual, emotional, and stylistic elements into a unified framework. The study provides actionable insights for marketers to optimize user interaction and opens avenues for further exploration of engagement strategies across digital platforms.